Шығыс пен Батыс аясындағы қазақ мәдениеті - Gabitov, T. H.; Alikbayeva, M. B.; Omirbekova, A. O. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The work is carried out within the framework of the research project of the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan «The Role and Place of Cultural Monuments in the Kazakhstani Modernization in the Context of Strategy 2050». The West and the East is an eternal opposition. If the East was represented in a number of historical researches as the area of general prosperity, erudition and enlightenment, or it was accented in the spirit of stagnation, slavery and poverty; that on the other hand the developed superiority of the West in the XIX and XX centuries in the technical and economic and strategic terms generated the illusion of the «inferiority» of the Eastern world in the minds of the certain circle of the European intellectuals that grants them the right of familiarizing the «inert» East to the benefits of civilization. Especially the view of the separate western and not only the western politicians unconvincingly represents that the eastern type of civilization, especially Muslim’s, during contacts with other civilizations and cultures finds the imperial tendencies to other sociocultural societies. This article discusses some aspects of the approach to pre-Islamic cultural heritage in the history of the spiritual quest of the Turkic peoples. There has been given comparative data analysis of the relationships of various ethnic cultures of their spiritual heritage. It has emphasized that respect for cultural heritage is a sign of civilization. Subjected to critical analysis of a variety of negative attitude towards the cultural heritage of the Kazakh people (Eurocentrism, ethnonihilism, particularism, fundamentalism, passeizm, etc.). Key words: Eurocentrism, globalization, cultural policy, cultural pluralism, sociocultural value.